AN ANTHROPOMORPHIC SPEECH PROCESSING BASED ON THE COCHLEAR MODEL AND ITS APPLICATION FOR CODING TASK - Petrovsky, A. A.; Likhachov, D. S.; Wan, W. (International Journal of Computing, 2014)
According to antisymmetry of basilar membrane (BM) movements, a new mathematical model of cochlea is derived using viscous cochlear fluid theory, and then transformed into a digital cochlear model with bilinear transformation. The frequency responses are found to be quite consistent with the experimental data, especially the high frequency slope is much more improved. A new cochlear map and 3 dB bandwidth characteristics for cochlear filter banks are obtained and presented, which will make applications of cochlear model more quantitative and accurate. Due to simplicity of its structure and reality of its characteristics, it will be proved the model can be used easily in speech processing system.